A Case of Neurosyphilis Presenting with Multiple Cranial Neuropathy - Eda Kılıç Çoban; Mehmet Ali Aldan; Sedat Gez; Nilüfer Kale; Mesude Özerden; Nazan Sakallı; Aysun Soysal (Türk Nöroloji Dergisi, 2016)
Syphilis is a sexually-transmitted disease caused by the spirochete bacterium Treponema pallidum. Central nervous system involvement can occur in every stage of the disease. It is classified into: acute syphilitic meningitis, meningovascular syphilis, and parenchymatous neurosyphilis. Acute basilar syphilitic meningitis is characterized primarily by the presence of cranial nerve involvement. As cranial nerve enhancement may be seen in a broad range of diseases, it can be the only clinical feature of neurosyphilis.